A Renewed Schengen Evaluation Mechanism in the Light of the Schengen Reforms - Zsákai, Lénárd (Magyar Rendészet, 2023)
The aim of the study is to identify the reasons, background and possible impacts of the international intention to reform the functioning of the Schengen area and to introduce a renewed Schengen evaluation and monitoring mechanism turned on by adopting a new Council regulation. In this article, the author examines the report from the Commission to the Council and the European Parliament on the functioning of the mechanism. The complex report presents comprehensive and detailed results of the first multi-annual evaluation programme, prepared and published by the European Commission in 2021, taking into account the feedback of Member States and relevant cooperating agencies and EU bodies. The study also examined two important elements of the Schengen renewal process, the EU strategy towards a fully functioning and resilient Schengen area and the preceding points of the new Scheval Regulation, which entered into force on 1 October 2021. The research concludes that recurring national shortcomings and divergent practices between Member States are likely to result from inconsistent implementation of the Schengen rules, which may have an impact on the overall functioning of the Schengen area as a whole. In addition to many other demands for change in the Schengen area, the states and EU institutions concerned have decided that the Schengen evaluation and monitoring mechanism needs to be renewed and undergo significant changes for the future. From a scientific point of view, the author concluded that in the field of law enforcement sciences, and especially in border management research, the renewal of the Schengen evaluation mechanism should be followed closely, as it is synergistic with several other related research issues (e.g. border management, border management education, etc.). With thorough research in this field, scientific works and scientific representation, the Hungarian law enforcement science is expected to be strengthened in the international scientific dimension.